Worksite Health Program Promoting Changes in Eating Behavior and Health Attitudes. Issue 6 (November 2015) - Mache, Stefanie; Jensen, Sarah; Jahn, Reimo; Steudtner, Mirko; Ochsmann, Elke; Preuß, Geraldine
Background . The aim of the present study was to evaluate the effectiveness of a worksite multicomponent health promotion intervention on eating behavior and attitudes, changes in body weight, and readiness to make eating behavior changes among workers over a 12-month intervention period. Method . A total of 3, 095 workers of a logistic company participated in a quasi-experimental comparison group study design. The intervention group received a multicomponent health training. Two of the main elements of the multicomponent intervention were physical exercise training and nutrition counseling/training. During the pilot year, participants completed a survey at baseline and again after 12 months to assess physical activity–, health-, and diet-related factors. Results . Results showed that participants' body weight did not significantly decrease in the intervention group. Mean weight loss in the intervention groups was 0.5 kg (body mass index = 0.1 kg/m 2 ). Eating behaviors in the intervention group improved more than in the comparison group. Some positive intervention effects were observed for the cognitive factors (e.g., changes in eating attitudes). Baseline readiness to change eating behavior was significantly improved over time. Conclusions . We demonstrated initial results of a long-term multicomponent worksite health promotion program with regard to changes in body weight, eating behavior, and attitudes. This evaluation of a 12-month pilot study suggests that a worksite health promotion program may lead to improvements in nutritional health behaviors for a number of workers. An investigation of long-term effects of this multicomponent intervention is strongly recommended.